Mortality rate and acute kidney injury prevalence reduction in COVID-19 critical patients treated with hemoperfusion (2024)
Introduction: Coronavirus disease 2019 (COVID‑19) induces organic damage mainly through the patient’s immune overreaction. Hemoperfusion (HPF) can remove infl ammatory cytokines and can reduce the negative effects of cytokine storm in COVID‑19. We compared the mortality rate, infl ammatory response, and acute kidney injury (AKI) prevalence among patients suffering from respiratory insufficiency secondary to COVID‑19 treated with and without HPF with HA330 cartridge. Methods: Mortality rate, serum creatinine, and ferritin values were compared between patients suffering from respiratory insufficiency secondary to COVID‑19 who received conventional treatment and another group of patients who additionally received four sessions of HPF with HA330. Results: Of 116 patients suffering from acute respiratory insufficiency secondary to severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2), one group (n: 84) received support treatment and the other group (n: 32) additionally received HPF with HA330 cartridge. Both groups had no renal disease and similar age and comorbidities at admission, except for obesity and mechanical ventilation requirement, which were significantly higher in the HPF group. Mortality rate (61% vs. 31%, P: 0.008), serum creatinine (1.4 vs. 0.5 mg/dl, P < 0.001), and post‑HPF serum ferritin (2868 vs. 1675, P < 0.001) were significantly lower in the HPF group. Conclusion: Mortality rate, serum ferritin, and AKI were significantly reduced in critical COVID‑19 patients who received HPF with HA330 cartridge than in those who did not receive it. These results were obtained despite the HPF group risk factors, such as obesity and mechanical ventilation, worsening its prognosis.